Aqueous two-phase systems based on cholinium salts and tetrahydrofuran and their use for lipase purification - Souza, Ranyere L
Aqueous two phase systems (ATPS) formed with cholinium based ionic liquid ILs (or salts) are a novel, low cost, and high efficient technique for the recovery of biomolecules. This study examines the formation of ATPS based on cholinium based salts (cholinium chloride, cholinium bitartrate and cholinium dihydrogencitrate) and tetrahydrofuran (THF) for the purification of lipase from Bacillus sp. ITP 001, produced by submerged fermentation. The optimum conditions for this purification were determined to be 40 wt% of THF and 30 wt% of cholinium bitartrate at 25 C. A purification factor of 130.1 ± 11.7 fold, a lipase yield of 90.0 ± 0.7% and a partition coefficient of enzyme for IL rich phase (KE 0.11 ± 0.01) and protein contaminants for THF rich phase (KP 1.16 ± 0.1) were achieved.